Strength Design Method of Reinforced Concrete Beam Elements along an Inclined Crack on the Transverse Forces and Bending Moments Joint Action - Dovzhenko, Oksana; Pohribnyi, Volodymyr; Shkurupiy, Oleksandr; Mytrofanov, Pavlo (International Journal of Engineering and Technology, 2018)
The forces scheme in the reinforced concrete elements inclined section is proposed under the transverse forces and bending moments joint action. The diagram shows the transverse and longitudinal forces perceived by the compressed concrete zone and longitudinal reinforcement, forces in the transverse reinforcement and engagement in an inclined crack. The truncated concrete wedge strength problem simulating a compressed zone over a dangerous inclined crack is solved on the plasticity theory basis. An engineering method for calculating the bending elements strength along an inclined crack is developed, which allows more fully to take into account the factors determining the strength influence and to achieve a reduction in the structures material consumption. To simplify the calculation in tabular form, the projection inclined section functions are given for various loading schemes.Â Â